2022
DOI: 10.3390/pharmaceutics14061199
|View full text |Cite
|
Sign up to set email alerts
|

WPI Hydrogels with a Prolonged Drug-Release Profile for Antimicrobial Therapy

Abstract: Infectious sequelae caused by surgery are a significant problem in modern medicine due to their reduction of therapeutic effectiveness and the patients’ quality of life.Recently, new methods of local antimicrobial prophylaxis of postoperative sequelae have been actively developed. They allow high local concentrations of drugs to be achieved, increasing the antibiotic therapy’s effectiveness while reducing its side effects. We have developed and characterized antimicrobial hydrogels based on an inexpensive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The samples containing only WPI (WPI_0) did not influence cell viability regardless of extract dilution (Figure 10), which confirm that WPI is cyto-compatible with MG-63 cells. Similar materials based on WPI have already been tested by Plastun et al [74] on L929 fibroblasts and by Norris et al [75] on MC3TC-E1 cells. Both studies found out that WPI-based materials were not cytotoxic against different cell types.…”
Section: Cytotoxicity Evaluationmentioning
confidence: 89%
“…The samples containing only WPI (WPI_0) did not influence cell viability regardless of extract dilution (Figure 10), which confirm that WPI is cyto-compatible with MG-63 cells. Similar materials based on WPI have already been tested by Plastun et al [74] on L929 fibroblasts and by Norris et al [75] on MC3TC-E1 cells. Both studies found out that WPI-based materials were not cytotoxic against different cell types.…”
Section: Cytotoxicity Evaluationmentioning
confidence: 89%
“…Particular attention is paid to emulsion systems intended for intravesical drug delivery due to their ability to immobilize both hydrophobic and hydrophilic molecules. Mucoadhesive emulsions are of increasing interest given the combination of properties which are beneficial for intravesical drug delivery. In our study, mucoadhesive emulsion microgels were prepared on the basis of a naturally derived component, whey protein isolate (WPI), which is a byproduct of whey in cheese production . WPI is being extensively studied as a hydrogel material for biomedical applications. Moreover, WPI can be used as an emulsifier and stabilizer to produce oil-in-water emulsions. The ultrasonication used for homogenization of emulsions promotes not only the emulsion formation but also the gelification of the WPI protein shell due to the WPI denaturation and the formation of a three-dimensional hydrogel network . The ability of WPI to attach to the tissue mucosa is used in pharmaceuticals to create mucoadhesive drug delivery forms, for example, Loramyc for the treatment of oral candidiasis .…”
Section: Introductionmentioning
confidence: 99%